Penilaian Estetika Produk Upcycling Karya Siswa SMK Tata Busana - Qisti Sentosa, Siti Aisyah; Listiani, Sri; Suryawati (Universitas Negeri Jakarta, 2025)
This study aims to assess the aesthetics of upcycling products made by students of the Vocational School of Fashion Design. The assessment is based on Djelantik's aesthetic theory, which includes aspects of form/appearance and appearance/presentation. The research methodology used in this study is quantitative with a Pre-Experimental one-shot case study design, involving 5 expert panelists who assessed 5 tote bag products with additional decoration using the embedding techniques. The results showed that the form/appearance aspect with the elements and principles of design obtained a score of 91.75%, which is included in the very good category. The appearance/presentation aspect which includes skills and facilities or media scored 96.3%, also included in the very good category. Overall, the aesthetics of additional decoration with sticking techniques on upcycling products by students received an average score of 94.25%, including in the very good category. According to the expert panelists, product 3 had the best results of adding decoration. In conclusion, the aesthetic assessment of additional decoration on upcycling products made by students of Vocational School of Fashion Design is very good. Keywords: Aesthetic Assessment, Upcycling, Embedding Technique, Vocational School of Fashion Design